ANALISIS PENERAPAN SAK ETAP (STUDI PADA KOPRASI KARYAWAN TIRTA DHARMA PDAM KOTA PONTIANAK) - .Rahmawati, Dy; Genjik, Bambang; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This thesis is titled "Analysis the Implementation of Financial Accounting Standards of Entities without Public Responbility (IFRSs) (Study of the PDAM Tirta Dharma Khatulistiwa Employee Cooperative of Pontianak)". The method used is descriptive method. Data collection techniques used is direct communication techniques and documentary study techniques. The data collection tool used interview guidelines and data contained in the archive owned by the PDAM Tirta Dharma Khatulistiwa Employee Cooperative Pontianak. The data analysis technique used is descriptive qualitative analysis. The results of this study showed that 1) The cooperative management in applying their financial statements does not refer to the Statement of Financial Accounting Standards No. 27 Cooperative Accounting because it only presents a Balance Sheet and Calculation of Operating Results (PHU), which should consist of a balance sheet, calculation of operating results (PHU), cash flow statements, member economic promotion reports, and notes to the financial statements. 2) In the application of the calculation of results of operations there is also an error in entering the name of the goods account, there are several accounts of goods that should help reduce income in the calculation of results of operations but not recorded cooperatives in the burden of cooperatives and in the calculation of results of operations also there is no separation of member income and non-members and operating expenses and cooperative expenses. 3) In the application of cooperative financial statements there are still errors in writing the name of the goods account and include it in the preparation of the report on writing also does not match the order in the financial accounting standards.Key words: Analysis the Implementation of Financial Accounting Standards of Entities without Public Responbility (IFRSs), Cooperative